PROBLEMATIKA PENANGANAN PERNIKAHAN DI MASA PANDEMI COVID-19 PERSPEKTIF HUKUM ISLAM DI KANTOR URUSAN AGAMA KECAMATAN TURATEA KABUPATEN JENEPONTO - Irwan; Hamzah Hasan; Muh. Jamal Jamil (Universitas Islam Negeri Alauddin Makassar, 2023)
The problem of handling marriage during the COVID-19 pandemic became a consideration for the Office of Religious Affairs (KUA) of Turatea District, Jeneponto Regency, in providing services. This research examines the problems of KUA in handling marriage during a pandemic from the perspective of Islamic law. This research is field research that describes the results of the discussion using descriptive qualitative methods, empirical juridical approaches, and normative theology. The results showed that the KUA of Turatea District had problems that were evident from the habits of the community, such as the lack of understanding of the community regarding COVID-19; the community did not report marriages; getting married at a marriage hall received a negative response; and the community was present on their initiative. Marriages carried out during a pandemic are legal according to Islamic law but still comply with health protocols so that harm is avoided as per the sadd al-dzariah rule.